(untitled) (CIPEEX, 2022)
Knee osteoarthritis, a common and progressive condition, is characterized by changes in articular cartilage and other anatomical structures (Primorac et al., 2020). Of congenital or acquired etiology, excess load (acute or chronic) or a combination of these (Felson et al., 2013). Cause of pain, functional limitation, and consequent decrease in quality of life (Silverwood et al., 2015). Knee arthroplasty is a surgical alternative for restoring joint function and quality of life in these patients (Argenson et al., 2013; Benedetto et al., 2019). For the evaluation of knee functional restoration and patient quality of life, objective and subjective modalities are available (Unnanuntana et al., 2018). The objective assessment of gait with inertial sensors has a significant correlation with the findings of performance tests and quality of life questionnaires and outcomes (Youn et al. 2020). The objective of this work is to evaluate the gait, functional capacity, and quality of life of patients undergoing primary knee arthroplasty between two types of knee prostheses: posterior stabilized with a fixed tibial plateau base and congruent rotating tibial plateau prosthesis for the treatment of advanced knee osteoarthritis.